Numerical simulations of blood flow in a stenosed artery using a multi-criteria decision-making Algorithm - Umar, Muhammad; Zeeshan, Muhammad; Rafiq, Shazia; Siddique, Imran; Shakoor, Bushra; Ghallab, Abdullatif Saleh (Springer Nature, 2025)
The hemodynamic characteristics of blood flow through a stenosed artery are analyzed in this study. A two-dimensional computational model is developed to simulate the behavior of a hybrid micropolar-Casson fluid flow with a magnetic field perpendicular to the flow, which mimics blood flow. The findings provide valuable insights into the complex dynamics of blood flow in narrowed arteries and help identify effective strategies for managing stenosis-related hemodynamic conditions. To optimize parametric values, a well-known technique called TOPSIS (Technique for Order Preference by Similarity to the Ideal Solution) is employed. TOPSIS enabled a systematic evaluation and ranking of the alternatives of parametric values from best to worst based on their similarity to the ideal solution. The values from derived rankings are graphically represented and validated, demonstrating that the rankings are robust and consistent. It is evident from the results that the Hartmann Number can be used to control the flow separation region. The wall shear stress has a direct relation with the Hartman number and Casson parameter. The heat transfer rate for the hybrid nano fluid escalates with increasing values of Hartman number, Darcy parameter, and Strouhal number. The outcomes of this research have potential implications for cardiovascular health and can aid in developing advanced diagnostic and therapeutic approaches for stenotic arterial diseases.